The Application of the Qiyas Method in Islamic Legal Reasoning: A Review of Fatwas by the Indonesian Ulama Council (MUI) - Waheeda, Waheeda; Mutakin, Ali; Aziz, Abdul; Nugraha, Iqbal Subhan; Saujan, Iqbal (RaSAIL Media Group, Semarang, Indonesia, 2025)
Fatwas have an important role in bridging the gap between the ideals of Islamic law and the ever-evolving social reality. This study examines the application of the qiyas method in fatwas issued by the Indonesian Ulema Council (MUI), focusing on its legal reasoning and relevance in contemporary contexts. Through a qualitative approach with content analysis techniques, this study examines several MUI fatwas that use the basis of qiyas, such as provisions on the prohibition of alcohol, the implementation of Friday prayers on ships, and the obligation of zakat on income. The results of the study show that qiyas is an important instrument for MUI in responding to modern problems by referring to analogies from classical Islamic texts. By adapting legal principles from the past to the present situation, MUI shows the flexibility of Islamic law in responding to the challenges of the times. This study confirms that qiyas not only functions as a classical method in fiqh proposals, but also remains relevant in formulating contextual and applicable fatwas. These findings show the dynamics of contemporary ijtihad and the importance of the role of scholarly institutions in maintaining the continuity between sharia and the needs of modern society.